CHARACTERISTICS OF DURIAN SEED BROWNIES WHICH ENRICHED WITH COCONUT FLOUR - Ade Heri Mulyati; Diana Widyiastuti; Ikhwanul Muslimin (Universitas Pakuan, 2019)
Durian seed flour is a product selected and used as a fixed variable in future studies. The results of chemical analysis and micro Brownies F2 have a water content of 26.47%, ash 1.63%, 16.56% fat, 6.91% protein, carbohydrates 48.43%,% dietary fiber, 4 ALT tests, 3 x 102 cabbage / g, e- coli 3, mold 10 Bacillus Cereus 100. In a subsequent study, Brownies steamed (F8) with a ratio of 75% wheat flour and seed flour 25% enriched 20% Durian pulp has the water content of 26.35%, ash 1.65%, 19.58% fat, 7.20% protein, carbohydrates 48.53 %, 12.53% dietary fiber, 2.7 x 102 ALT test cabbage / g, e-coli 3, mold 10 Bacillus Cereus 100. The shelf life of the conventional product at room temperature (28-30oC), Brownies control F1 has the shelf life of 3 days while the Brownies F8 is 6 days, the engine coolant (2- 8oc) Brownies control F1 has the shelf life of 10 days while Brownies F8 14 days.